A Literature Review of Forensic Linguistics - Mirsa Umiyati (IJFL (International Journal of Forensic Linguistic), 2020)
Speech is an activity to express the ideas or thoughts. Speech is an oral communication delivered by someone which had a certain purposes. It is whether to persuade, to entertain, or to give information. To express the ideas or thoughts, the language is needed. Speech and language are two fields that play role in human communication. Speech and language cannot be separated to each other. In delivering the speech, the language must be considered. The law issues that occurred by language in speech is possible to use forensic linguistics to investigate the language used in speech. The objective of this research is to review a literature of forensic linguistics. This research used descriptive qualitative method. The data of this research are some books related to forensic linguistics. As a result of analysis, it is showed that forensic linguistics as the interdisciplinary field which examines, defines, and investigates language in court as evidence to polices, judges and lawyers. Some text types of forensic linguistics are emergency call, ransom demands and other threat communications, suicide letters, final death row statements, confessions and denials by public figures. Moreover, several areas of forensic linguistics that can be investigated in law issues are auditory phonetics, acoustic phonetics, interpretation of expressed meaning (semantics), interpretation of inferred meaning (discourse and pragmatics), stylistics and questioned authorship, language of the law, language of the courtroom, interpretation and translation.